Nilai-Nilai Pendidikan Di Dalam Teks Pantun Batobo Masyarakat Desa Seberang Pantai Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi Provinsi Riau - Ferdinan, Ferdinan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2023)
This study aims to document the singing of Batobo rhymes as an oral literary study to explain the form of educational values in Batobo rhymes. This research is qualitative research using descriptive analysis method. The descriptive analysis method is in accordance with its essence, namely the data that has been collected is then selected, grouped, studied, interpreted, and concluded. The results of this study are the Batobo rhyme songs of the people of Seberang Pantai Village, and the Batobo rhyme songs contain the following forms of educational values. (1) educational values related to the form of the values of responsibility, with indicators of attitude and behavior of being disciplined, tenacious, and willing to take risks. (2) educational values related to forms of social care, with indicators of attitudes and behavior of affection, politeness, friendship/communicativeness, social care, and love of family. (3) educational values related to the form of values of honesty, with indicators of responsible attitude and behavior, fulfilling obligations, being generous, keeping promises, speaking as it is, and being democratic. (4) educational values related to the form of friendly/communicative values, with indicators of being honest, affectionate, speaking as it is, keeping promises and being responsible.